2015
DOI: 10.1111/gcb.12990
|View full text |Cite
|
Sign up to set email alerts
|

Elevated temperature is more effective than elevated [CO2] in exposing genotypic variation in Telopea speciosissima growth plasticity: implications for woody plant populations under climate change

Abstract: Intraspecific variation in phenotypic plasticity is a critical determinant of plant species capacity to cope with climate change. A long-standing hypothesis states that greater levels of environmental variability will select for genotypes with greater phenotypic plasticity. However, few studies have examined how genotypes of woody species originating from contrasting environments respond to multiple climate change factors. Here, we investigated the main and interactive effects of elevated [CO2 ] (CE ) and elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 72 publications
2
8
0
Order By: Relevance
“…In the present study, ET significantly increased the net photosynthesis rate (Pn), total chlorophyll ab (Tchl), Fv/Fm and SLA of both conifers (Figure 3), indicating that ET had a positive influence on the photosynthetic capacity and growth (see also Xu et al 2008, Fu et al 2015, Huang et al 2015, Reich et al 2018, Yuan et al 2018. This was further supported by the mesophyll cell structure of leaves that showed that both conifers exhibited smooth and continuous cell membranes and a typical chloroplast structure under ET.…”
Section: Competition and Elevated Temperature Affect Photosynthetic Csupporting
confidence: 74%
See 1 more Smart Citation
“…In the present study, ET significantly increased the net photosynthesis rate (Pn), total chlorophyll ab (Tchl), Fv/Fm and SLA of both conifers (Figure 3), indicating that ET had a positive influence on the photosynthetic capacity and growth (see also Xu et al 2008, Fu et al 2015, Huang et al 2015, Reich et al 2018, Yuan et al 2018. This was further supported by the mesophyll cell structure of leaves that showed that both conifers exhibited smooth and continuous cell membranes and a typical chloroplast structure under ET.…”
Section: Competition and Elevated Temperature Affect Photosynthetic Csupporting
confidence: 74%
“…Changed biomass allocation may be a way to improve plants' responses to climate change (Huang et al 2015). For example, a meta-analysis conducted by Yuan et al (2018) showed that warming has no effect on biomass allocation between roots and shoots, while Wertin et al (2011) and Duan et al (2018) reported that warming induces increased or decreased allocation to roots.…”
Section: Introductionmentioning
confidence: 99%
“…Species identity of plants and lichens are known to play an important role in regulating responses of soil microbial community and ecosystem functions to global climate factors, including increasing temperature, nitrogen deposition and changes in water availability, mainly through root exudation or altered microclimate (Haichar et al, 2008;Liu et al, 2016;Yuan et al, 2016). Previous studies suggested that there was intraspecies variation in plant response to climate change including elevated CO 2 and warming via altered traits such as photosynthetic capacity, leaf area and growth (Drake et al, 2015;Huang et al, 2015). In theory, different provenances of the same species can differentially impact both microbial community and soil functions (Johnson et al, 2012;Leff et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Many temperature manipulations have been conducted to quantify growth and physiological responses ( Gimeno et al, 2012 ; Huang et al, 2015 ). However, because most studies focus on responses of individual tree species, we have little understanding of how warming would affect co-occurring species.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely recognized that plants must achieve a balance between carbon assimilation, carbon storage and growth, all of which are directly or indirectly affected by climate warming ( Smith and Stitt, 2007 ). The concentration of non-structural carbohydrates (NSC) within plant tissues, which depends on the balance between carbon supply (i.e., photosynthesis) and carbon demand (i.e., growth) ( Michelot et al, 2012 ), were considered to decrease under short-term warming ( Huang et al, 2015 ). Therefore, it is necessary to study the interaction among carbon assimilation rate, plant biomass and NSC under warming.…”
Section: Introductionmentioning
confidence: 99%